MRSA: the Relationship Between Animal Source Foods (ASF) and Humans– a One Health Concern - Crippa, Bruna Lourenço; Camargo, Carlos Henrique; Rall, Vera Lúcia Mores [UNESP]; Silva, Nathália Cristina Cirone (Springer Nature, 2025)
Purpose of ReviewThis review presents an overview of methicillin-resistant Staphylococcus aureus (MRSA) transmitted by various Animal Source Foods (ASF), its transmission route, and the importance of its monitoring within the One Health approach. Therefore, this review demonstrates the importance of this microorganism, its relationship with animals and humans, food, and its control.Recent FindingsRecent research indicates that MRSA can occur in various animal species, including pigs, poultry, cattle, horses, and sheep. Human-to-human transmission has been detected on nearly every continent, spanning several countries. Furthermore, the spread of MRSA also extends to animal-source foods (ASF), which are also considered a route of dissemination; posing as a public health concern, given the serious health problems that MRSA can cause.SummaryMethicillin-resistant Staphylococcus aureus (MRSA) is a major public health concern due to its resistance to commonly used antibiotics, which complicates treatment in both humans and animals. MRSA transmission from animal-source food (ASF) to humans is a critical route of exposure, especially in agricultural settings, where antibiotics are often overused. Recognizing the connection between human, animal, and environmental health, the One Health approach is crucial for addressing the spread of MRSA. This review explores MRSA prevalence in ASF and its relationship with the One Health framework.